Problems of Representing Isohyet Maps in Al-Musayyib District and Methods of Their Resolution Using Geographic Information Systems (GIS) - Dr. Saad Thamir Ibrahim (Journal of College of Education, 2026)
The study aims to identify the key challenges encountered by researchers in the cartographic representation of climatic elements, specifically precipitation, and to propose solutions in line with cartographic principles. In the designed map, several issues were observed. Notably, only a single ground observation point, located at Al-Hilla, was used to represent rainfall amounts. This point is situated far from the map’s central area; consequently, during the spatial interpolation process, points with minimal influence are effectively excluded, resulting in reduced accuracy of the rainfall map. To improve precision, it is recommended to increase the number of input points, i.e., additional ground observation stations within the study area, to enhance the reliability of the cartographic representation. Furthermore, careful selection of an appropriate quantitative legend is essential when designing line-symbol maps, ensuring that the legend accurately reflects the statistical values being represented. Attention should also be given to the scale and size of the base map to optimize map readability and accuracy.
Keywords: Cartographic problems, cartographic representation, ground-based observation, isohyets